The study of hyponatremia in the prognosis of acute ischemic stroke - Y. N., Narayana Swamy; Gowda, Manoj; Khalid, Mohammed S. (International Journal of Advances in Medicine, 2019)
Background: Stroke is defined as an abrupt onset of a neurologic deficit that is attributable to a focal vascular cause. Acute ischemic stroke is the fourth leading cause of death and most common cause of long-term disability worldwide. Hyponatremia is the commonest electrolyte disturbance encountered in the neurological intensive care units. This study investigated to evaluate hyponatremia in acute ischemic stroke patients as a reliable prognostic marker on admission to ICU. Methods: A total of 150 patients admitted to M S Ramaiah Hospitals during the period of October 2014 to September 2016 who fulfilled the inclusion criteria were considered in the study. All patients were evaluated by neurologist/ physician and the diagnosis of Acute ischemic stroke was made by Clinical examination and confirmed by Computed Tomography (CT) and/ Magnetic resonance imaging (MRI) brain. Hyponatremia was defined as serum sodium level <135 mmol/L and recorded on admission. Outcome was assessed by National Institute of Health Stroke Scale (NIHSS) score at admission, day 5 and at discharge, duration of ICU stay, duration of hospital stay and in-patient mortality. Results: Among the 150 patients admitted with acute ischemic stroke, mean age was 60 years, 68% were males and 36% patients had hyponatremia. Baseline characteristics were similar between groups except for gender distribution (p=0.037). Hyponatremic patients had higher NIHSS score on admission, on day 5 and at discharge (p=<0.001). Hyponatremic patients had a longer duration of ICU stay (p=<0.001) and in hospital stay (p=<0.001). Hyponatremia was associated with higher mortality in hospital (p=0.026). Conclusions: Study demonstrates that hyponatremia at admission in acute ischemic stroke patients is associated with acute mortality, worse NIHSS score at admission and at discharge, and longer duration of ICU and hospital stay.